The Impact of the Banking Sector Development on Agricultural Development: The Case of Cameroon - Tamga, Mireille Rachel Djuissi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Despite the toughness of the competition, Cameroonian agricultural products have succeeded to stand out against the rival products by their quality. Financial investors want to be sure that the agricultural products will generate sufficient funds over years to cover up their debt services and their operating expenses. Therefore, the main question we need to answer is: how the valorization and expansion of the banking sector can positively impact agriculture in Cameroon? The main objective of our study is to highlight the positive effects of the banking sector on agriculture in Cameroon. The main hypothesis is that the development of banking sector influences the development of agriculture in Cameroon. Our analysis will be done using two types of time series data, namely agriculture value added, and domestic credit to private sector. After analysis, our two variables are stationary at first level under ADF and PP. Johansen test concludes that there is a long run relationship amongst the variables. After running the lag length structure, outputs disclose that our optimal results will be reached on lag4. After running VECM test, results show a short and long run relationships between our two variables. And finally, the Granger causality test enables us to conclude that there is a bidirectional relationship amongst the variables. Keywords: Agriculture value added, Domestic credits, Cameroon

Öz: Kamerun tarım ürünü ürünleri kalitesiyle öne çıkmayı başarmıştır. Bu durumdan dolayı, finansal yatırımcılar, tarım ürünlerinin borç servisini karşılamak ve işletme masraflarını karşılamak için yeterli fon yaratacağı konusunu gündeme getirmektedir. Bu nedenle cevaplamamız gereken asıl soru, kamulaştırmada bankacılık sektörünün genişlemesinin tarımı nasıl olumlu etkileyebileceğidir. Çalışmamızın temel amacı, Kamerun'da bankacılık sektörünün tarımda yarattığı olumlu etkileri vurgulamaktır. Ana hipotez ise: Kamerun'da bankacılık sektörünün gelişimi tarımın gelişimini nasıl etkiledigi noktasındadır. Analizlerimiz, tarımsal katma değer ve özel sektöre verilen iç kredi olmak üzere iki zaman serisi verisi kullanılarak yapılmaktadır. Analiz sonrasında, iki değişkenimiz ADF ve PP altındaki birinci seviyede durağandır. Johansen testi, değişkenler arasında uzun vadeli bir ilişki olduğu sonucu göster mektedir. VECM testini yaptıktan sonra, iki değişkenimiz arasında kısa ve uzun vadede bir ilişki olduğu tespit edilmiş ve Granger nedensellik testi, ile değişkenler arasında çift yönlü bir ilişki olduğu sonucuna ulaşmaktayız. Anahtar kelimeler: Tarım katma değer, Yerli krediler, Kameru
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2017. Supervisor: Assoc. Prof. Dr. Nesrin Özataç.
Keywords: Banking and Finance; Acriculture; Agricultural Products; Financial Development; Cameroon; Agricultural Credits; Rural Credits; Agriculture Value Added; Domestic Credits